2006
DOI: 10.1111/j.1365-2934.2006.00625.x
|View full text |Cite
|
Sign up to set email alerts
|

Staff satisfaction with work, perceived quality of care and stress in elderly care: psychometric assessments and associations

Abstract: There was support for the instruments' validity and reliability. Older age, higher scores/satisfaction with workload, cooperation, expectations and demands, personal development and lower scores on internal motivation contributed to less stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 33 publications
2
60
1
1
Order By: Relevance
“…The role of "intrinsic motivation" is less clear. In some studies "intrinsic motivation" was related to greater stress [25], but in others motivation along with a good acceptance of changes were related to better job satisfaction [2]. As expected, we found "intrinsic motivation" to be a consistent resource to copy changes over time.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The role of "intrinsic motivation" is less clear. In some studies "intrinsic motivation" was related to greater stress [25], but in others motivation along with a good acceptance of changes were related to better job satisfaction [2]. As expected, we found "intrinsic motivation" to be a consistent resource to copy changes over time.…”
Section: Discussionsupporting
confidence: 74%
“…In some studies it seems to protect against job stress [25], while in others this increases over time in practice [27]. Perhaps there are other factors, not measured in this study, which could increase with time and could improve job control, such as the position in the team and social support.…”
Section: Discussionmentioning
confidence: 86%
“…Although a number of articles identified in this review have confirmed significant relationships between work related stressors and burnout [25,26,27,28,29,30,31,32,33,34,59,60,77,78], job satisfaction [11,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,58,59,60,61,62,63,64,65,66,81] as well as general health, these relationships are predominantly two way relationships with only a handful of studies confirming three way relationships [64,65,71,84]. Among the studies confirming two way relationships, only one study confirming the relationship between job satisfaction and general health [85] was identified.…”
Section: Discussionmentioning
confidence: 86%
“…Work related stressors including job complexity, feedback/clarity, leadership styles, opportunities for promotion and growth, autonomy, workload [74,75,76], relations with the head nurse, peers and physicians, job conflict, cooperation, expectations and demands, development and motivation are related to job satisfaction and health complaints [77,78]. Contrary to this, other findings suggest that higher stress levels among nurses were associated with more health complaints but not with job satisfaction [79].…”
Section: Resultsmentioning
confidence: 99%
“…The total score was used in the present study, and responses are rated on a 7-point scale. Stress symptoms were investigated using the factor "perceived stress symptoms" (10 items) from the Psychosomatic Health Aspect Scale (Engstrom, Ljunggren, Lindqvist, & Carlsson, 2006). The responses are rated on a 5-point scale.…”
Section: Measurementsmentioning
confidence: 99%